Professional competence of future educators: theoretical approaches to its formation on the basis of competence approach - Kovrey, Dora; Bobyrieva, Olena (Social work and education, 2022)
The modern preschool educational establishment has been actively becoming an "institution of socialization", and the educator must be an example for children and have the appropriate level of professional competence. It has been established that from the psychological and pedagogical point of view a professionally competent educator has deep knowledge, has developed pedagogical abilities, perfect professional skills, formed professional self-awareness and pedagogical thinking, as well as skills of self-learning and self-improvement. It has been found that the main characteristics of the professional competence of future educators are: perfect mastery of theoretical knowledge; pedagogical skills; self-improvement and creative work on oneself; mastering cultural, ethno-spiritual potential; using of the newest methods of training and education of children of preschool age. There are five main functions in the professional activity of an educator: organization, planning, control and assistance, pedagogical analysis. To the range of main roles of an educator we include: teaching, helping children to acquire new knowledge, and educating on the basis of creative motivation. An important role in the professional competence of educators has given to personal qualities (openness, friendliness, empathy, sincerity). A modern educator must be an innovative researcher, organizer, facilitator, consultant, and coach.The leading role in the formation of professional competence of future educators has been played by the competence approach. This approach is a fundamental methodological guideline, because it allows you to make a holistic, integrated view about the activities of the educator. Its implementation will provide knowledge, activity, and motivational readiness, promote the formation of creativity and encourage reflection. The competency approach will allow students to improve the methodology of implementation of didactic, educational, developmental and socializing interactive technologies in preschool educational establishments.